2020
DOI: 10.1063/5.0025978
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the electronic structures in different phases of gadolinium sesquioxides performed by electron energy loss spectroscopy

Abstract: The gadolinium sesquioxide (Gd2O3) with its bandgap of ∼5.4 eV and high dielectric permittivity and refractive index has been used widely in optics, magnetic resonance imaging, and high k dielectrics. Electron energy loss spectroscopy (EELS) reveals spectral features at 13.5 eV and 15 eV, which can be interpreted as surface and volume plasmons, respectively. The unusual surface exciton polariton, with surface resonances associated with excitonic onsets, was also observed at ∼7.5 eV. Because of the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Both phase purity and crystallinity of the synthesized m-Gd 2 O 3 were confirmed by X-ray diffraction (XRD) in the previous report. 14 Because the β angle between the (100) and (001) planes for m-Gd 2 O 3 is ∼100.13°, it is essential to obtain electron diffraction (ED) patterns and related TEM and STEM images along the [010] orientation, which displays this characteristic β angle. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both phase purity and crystallinity of the synthesized m-Gd 2 O 3 were confirmed by X-ray diffraction (XRD) in the previous report. 14 Because the β angle between the (100) and (001) planes for m-Gd 2 O 3 is ∼100.13°, it is essential to obtain electron diffraction (ED) patterns and related TEM and STEM images along the [010] orientation, which displays this characteristic β angle. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the O K-edge exhibited distinct differences in both the spectral features and energies due to the different Gd and O coordination and Gd–O bond lengths. 14 Furthermore, Shu et al also reported some differences in the low-loss region between c- and m-Gd 2 O 3 , however, without detailed analysis for m-Gd 2 O 3 . 14 Besides, Gd 2 O 3 has a larger bandgap of about 5.3 eV and the interband transitions generating weakly bound delocalized excitons presumably of the Wannier–Mott type readily build up collective resonances at the material surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(d)]. Combining with both STEM-EELS spectra and EFTEM-SI intensity maps, the spectral feature at ~7 eV peak can be considered as a surface resonance associated with excitonic onsets understood as surface exciton-polaritons (SEPs) [4]. In contrast to VP at 15 eV, the spectral intensity at 36 eV peak decreases when position electron probe from the material interior to the specimen edge, and then vanished when the electron probe is positioned at 2 nm away from the material surface as shown in Fig.…”
Section: Technology United Statesmentioning
confidence: 99%
“…Unlike the exponentially decaying in intensity as a function of q values for both SPs and VPs, the intensity of the spectral peak at ~36 eV increases as a function of q which implies the involving multiple scattering processes as described in ref. [4].…”
Section: Technology United Statesmentioning
confidence: 99%